Surface Imprinting Approach on Screen Printed Electrodes Coated with Carboxylated PVC for Myoglobin detection with Electrochemical Transduction - Moreira, Felismina T. C. (2015)
A novel surface molecularly-imprinted (MI) material to detect myoglobin (Myo) using gold screen printed electrodes (SPE) was developed. The sensitive detection was carry out by introducing a carboxylic polyvinyl chloride (PVC-COOH) layer on gold SPE surface. Myo was attached to the surface of gold SPE/PVC-COOH and the vacant spaces around it were filled by polymerizing acrylamide and N,N-methylenebisacrylamide (cross-linker). This polymerization was initiated by ammonium persulphate. After removing the template, the obtained material was able to rebind Myo and discriminate it among other interfering species. Various characterization techniques including electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) confirmed the surface modification. This sensor seemed a promising tool for screening Myo in point-of-care.